A study on new consolidation services in United Seino Transportation (Malaysia) Sdn. Bhd. / Ahmad Qahar Yusoff - Yusoff, Ahmad Qahar (1996)
Among the purpose of this research is to study overall performance of the United Seino Transport (Malaysia) Sdn. Bhd in implementing a new consolidation services. This research attemps to find ways in providing efficient consolidation services and at the same time minimizing the total distribution cost. Since prompt delivery is a main key to be a reliable transporter in a competitive market, it is important that the new consolidation services is well scheduleled with a proper planning of manpower especially driver in order to give reliable, punctual and efficient services. Comparison are also made between different transporters to find out either the transportation rates imposed by UST is in the same range or standard as imposed by other transporter. This study is also done to analyze the UST's trucks capacity in order to cope with customer order. From here, we can know either the existing UST's trucks is adequate with the demand or UST have to use outside trucks if the demand exceed the company capacity.